2021
DOI: 10.21926/obm.icm.2201010
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Sets for Muscle Hypertrophy: A Short Review †

Abstract: Cluster-set resistance training is focused on performance improvements of sports by increasing the repetition maximum, jump height, and efficiency in the sprint. In this commentary, we present relevant aspects to optimize the use of cluster training under the context of muscle hypertrophy. Therefore, we address intra-sets pauses, the number of repetitions per block, and strategies that benefit this methodology. During a cluster set resistance training program, not only the total number of repetitions could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…For example, cluster set configurations have been implemented in resistance training to optimize sports performance (Tufano et al, 2017 ). Although cluster-set resistance training protocols are more oriented to increase performance and strength levels, they may also be a useful tool to increase total training volume which has been found as the main training stimuli behind muscle hypertrophy (Vargas-Molina et al, 2021 ). A cluster set resistance training method is applied in 3–5 RM blocks, with a total of 3–4 blocks, and intra-set rest periods are between 20 and 30 s. We have previously demonstrated that four blocks of 3RM with 20 s of intra-set pause were more effective for increasing fat-free mass evaluated by DXA compared to four blocks of 3RM with 40 s of intra-set pause or two blocks of 6RM with 20 s of intra-set pause in healthy resistance-trained men (Vargas-Molina et al, 2020 ).…”
Section: Non-traditional Resistance Trainingmentioning
confidence: 99%
“…For example, cluster set configurations have been implemented in resistance training to optimize sports performance (Tufano et al, 2017 ). Although cluster-set resistance training protocols are more oriented to increase performance and strength levels, they may also be a useful tool to increase total training volume which has been found as the main training stimuli behind muscle hypertrophy (Vargas-Molina et al, 2021 ). A cluster set resistance training method is applied in 3–5 RM blocks, with a total of 3–4 blocks, and intra-set rest periods are between 20 and 30 s. We have previously demonstrated that four blocks of 3RM with 20 s of intra-set pause were more effective for increasing fat-free mass evaluated by DXA compared to four blocks of 3RM with 40 s of intra-set pause or two blocks of 6RM with 20 s of intra-set pause in healthy resistance-trained men (Vargas-Molina et al, 2020 ).…”
Section: Non-traditional Resistance Trainingmentioning
confidence: 99%